Lactate dehydrogenase levels predict coronavirus disease 2019 (COVID-19) severity and mortality: A pooled analysis - Henry, Brandon Michael; Aggarwal, Gaurav; Wong, Johnny; Benoit, Stefanie; Vikse, Jens; Plebani, Mario; Lippi, Giuseppe (The American journal of emergency medicine, 2020)
Coronavirus disease 2019 (COVID-19) infection has now reached a pandemic state, affecting more than a million patients worldwide. Predictors of disease outcomes in these patients need to be urgently assessed to decrease morbidity and societal burden. Lactate dehydrogenase (LDH) has been associated with worse outcomes in patients with viral infections. In this pooled analysis of 9 published studies (n = 1532 COVID-19 patients), we evaluated the association between elevated LDH levels measured at earliest time point in hospitalization and disease outcomes in patients with COVID-19. Elevated LDH levels were associated with a ~6-fold increase in odds of developing severe disease and a ~16-fold increase in odds of mortality in patients with COVID-19. Larger studies are needed to confirm these findings.